Optimalisasi Potensi Tanaman Herbal Lokal Melalui Pelatihan Pembuatan Minyak Gosok di Desa Petiro, Kabupaten Poso - Joni Tandi; Tien Wahyu Handayani; Vivi Gretia Triposa (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The use of herbal plants in modern medicine is increasing, notably for their antioxidant properties that effectively reduce free radicals. The growing "back to nature" trend, coupled with the high cost of modern pharmaceuticals, has encouraged communities to seek safer alternative treatments. This community service program was designed to enhance the capabilities of residents in Petiro Village, East Pamona District, Poso Regency to independently produce herbal massage oil as a sustainable health solution. Methodologically, the program employed a combination of lectures, practical demonstrations, and interactive discussions. Evaluation was conducted through pre-tests and post-tests administered to 22 participants to measure knowledge acquisition. The implementation process followed a systematic approach: preparation of raw materials, processing them into dry simplicia, and formulating massage oil using essential oils combined with natural herbs including ginger, turmeric, red betel leaf, garlic, and onion. Results demonstrated a remarkable improvement in community understanding, rising from 25% to 100% following the training intervention. This improvement encompassed comprehensive knowledge of the benefits, production techniques, and understanding of herbal massage oil ingredients. The training successfully fostered practical skills that participants could immediately apply. The significant knowledge transfer achieved has important implications for developing local herbal massage oil production as a sustainable enterprise, potentially improving both community health outcomes and economic prosperity in rural communities. Additionally, this initiative contributes to preserving traditional herbal knowledge while adapting it to contemporary health needs, creating a viable model for other rural communities seeking health self-sufficiency.